2011
DOI: 10.1016/j.brainres.2010.11.092
|View full text |Cite
|
Sign up to set email alerts
|

Increased BOLD activation to predator stressor in subiculum and midbrain of amphetamine-sensitized maternal rats

Abstract: Amphetamine, which is known to cause sensitization, potentiates the hormonal and neurobiological signatures of stress and may also increase sensitivity to stress-inducing stimuli in limbic areas. Trimethylthiazoline (5 μL TMT) is a chemical constituent of fox feces that evokes innate fear and activates the neuronal and hormonal signatures of stress in rats. We used blood oxygen level dependent (BOLD) MRI to test whether amphetamine sensitization (1 mg/kg, i.p. X 3 days) in female rats has a lasting effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
7
1
Order By: Relevance
“…Similarly, lesions of the lateral amygdala, which is important in context dependent fear conditioning, does not reduce the expression of unconditioned fear response to a predator (Wallace and Rosen, 2001). We also expected an outcome partly consistent with previous fMRI work using TMT as the predator stimulus (Febo and Pira, 2011). In the previous study, several brain areas showed greater BOLD percent changes with TMT than BA.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, lesions of the lateral amygdala, which is important in context dependent fear conditioning, does not reduce the expression of unconditioned fear response to a predator (Wallace and Rosen, 2001). We also expected an outcome partly consistent with previous fMRI work using TMT as the predator stimulus (Febo and Pira, 2011). In the previous study, several brain areas showed greater BOLD percent changes with TMT than BA.…”
Section: Discussionsupporting
confidence: 86%
“…Most of the areas were cortical and regions such as the BNST, amygdala, septum and prefrontal cortex did not distinguish between BA and TMT. This differs somewhat from Chen et al (2009), which measured the BOLD signal response to TMT in female rats and reported increased in BOLD in BNST, septum, hypothalamic nuclei, hippocampus, in addition to similar regions reported in the present study and in Febo and Pira (2011). However, Chen et al (2009) did not include a control odor during scanning which makes it difficult to compare the studies and to discern whether the pattern of BOLD signal changes corresponds to innate fear circuitry or the neural response to an aversive odor.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Several studies on the relationship between stress and psychostimulants in rodents were able to show cross-sensitization between repeated stress and repeated exposure to amphetamine ( Antelman et al, 1980 ; Kalivas et al, 1986 ; Hamamura and Fibiger, 1993 ; Febo and Pira, 2011 ; Booij et al, 2016 ). It is known that stress preferentially stimulates dopamine release in mesolimbic projection ( Horger and Roth, 1996 ) and frontal areas ( Lataster et al, 2011 ) and that glucocorticoids modulate the sensitivity of mesencephalic dopaminergic neurons to drugs of abuse ( Sorg and Kalivas, 1991 ; Deroche et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…It will be important in future work to determine the sensory cues provided by pups that can drive these regions of the brain to initiate maternal behaviours. We have already begun experiments using specific neurochemicals that can provide social signals (98). Rodents rely to a large extent on odours such as urine, pheromones and sounds within the ultrasonic range, and these are especially important for the maternal brain.…”
Section: Activation Of Reward Regions With Suckling Stimulation and Cmentioning
confidence: 99%